Investigating the impact of exposure to degraded natural environments on working memory through photographic stimuli - Dao, Truc Anh, author; Steger, Michael, advisor; Aloise-Young, Patricia A., committee member; Dik, Bryan J., committee member; LoTemplio, Sara, committee member (Colorado State University. Libraries, 2025)
The benefits of nature on human well-being have been well-documented under the umbrellas of several theoretical frameworks. Such research is often used to encourage people to go on walks in nature or in other ways become immersed in natural surroundings. However, beyond the fact that a good number of studies often use only photographic stimuli to simulate nature exposure, they have employed nature stimuli that are high in valence and low in arousal, as well as used urban stimuli that are average or low in both valence and arousal as a comparison. Such practices make it difficult to isolate the effects of nature and emotions on outcome measures in those studies. The use of mostly intact beautiful nature in these studies also suggests a gap in understanding how humans interact with damaged nature, especially the impact of damaged nature on humans. As the likelihood of people experiencing changes in their living environments increases with the rate of climate change, there is a need to better understand the influence of degraded nature on well-being in an experimental setting. Thus, the current project addressed two concerns: the lack of a set of image stimuli that can be used for environmental studies with various ratings of valence and arousal, and the limited investigation about the impact of damaged nature on working memory. Study 1 was conducted to obtain ratings of valence, arousal, sense of restoration, and preference on 780 images depicting scenes of built, intact natural, and degraded natural environments. Results affirmed intact natural environments are generally preferred, perceived as restorative, and associated with positive affect and low arousal. In contrast, degraded natural environment scenes are not preferred, associated with reduced restoration, low affect, and heightened arousal. Using images that were counterbalanced for valence, arousal, sense of restoration, and preference, Study 2 implemented an experimental design to examine the impact of types of environments on participants' working memory capacity. Findings revealed participants who viewed images of degraded environments performed worse on a working memory task at Time 2 compared to those who viewed images of intact environments. Notably, this effect emerged even when participants did not fully comprehend the content of the degraded nature images.